Models of pilot behavior and their use to evaluate the state of pilot training - Jirgl, Miroslav; Jalovecký, Rudolf; Bradáč, Zdeněk (Faculty of Electrical Engineering and Information Technology, Slovak University of Technology, 2016)
This article discusses the possibilities of obtaining new information related to human behavior, namely the changes or progressive development of pilots‘ abilities during training. The main assumption is that a pilot’s ability can be evaluated based on a corresponding behavioral model, whose parameters are estimated using mathematical identification procedures. The mean values of the identified parameters are obtained via statistical methods. These parameters are then monitored and their changes evaluated. In this context, the paper introduces and examines relevant mathematical models of human (pilot) behavior, the pilot-aircraft interaction, and an example of the mathematical analysis.

This article discusses the possibilities of obtaining new information related to human behavior, namely the changes or progressive development of pilots‘ abilities during training. The main assumption is that a pilot’s ability can be evaluated based on a corresponding behavioral model, whose parameters are estimated using mathematical identification procedures. The mean values of the identified parameters are obtained via statistical methods. These parameters are then monitored and their changes evaluated. In this context, the paper introduces and examines relevant mathematical models of human (pilot) behavior, the pilot-aircraft interaction, and an example of the mathematical analysis.
Models of pilot behavior and their use to evaluate the state of pilot training
Keywords: Pilot model; modeling of human behavior; identification; MATLAB; flight simulator; Pilot model; modeling of human behavior; identification; MATLAB; flight simulator